Monitoring and analysis of disinfection by-products in swimming pool waters - Wyczarska-Kokot, Joanna; Mendakiewicz, Jerzy (Instal, 2023)
The operation of swimming pool water treatment systems must provide a safe environment for the health of bathers. This is extremely important in the context of closed-loop pool water treatment, where concentrations of dissolved contaminants, including disinfection by-products (DBP), can occur. Monitoring and analysis of the indicator quantities of DBP (combined chlorine, total THM, chloroform) make it possible to ascertain their dependence on the operational parameters of a given pool circuit and the physicochemical parameters of water quality. Thematic studies were carried out for water samples from nine swimming pools with different functions. The treatment technology in all the pools was the same (pressure filtration in anthracite-sand bed filters and two-stage disinfection – UV irradiation and dosing with sodium hypochlorite solution). Concentrations of combined chlorine ranged from 0.05 mg Cl2/dm3 to 1.13 mg Cl2/dm3. Total THM concentrations ranged from 0.013 mg/dm3 to 0.053 mg/dm3. Based on the correlation coefficients determined, the DBP content was found to be significantly influenced by the load of bathers (m3/person), water temperature, permanganate index and absorbance values, and free chlorine concentration. An increase in the values of the analysed physicochemical water quality parameters (except pH) and an increase in the load of bathers also resulted in an increase in DBP content.
Keywords: swimming pool water; disinfection by-products (DBP); trihalogenomethanes; chloroform; combined chlorine; pool water quality monitoring